2020
DOI: 10.2147/ott.s232876
|View full text |Cite
|
Sign up to set email alerts
|

<p>Lung Cancer Cells Derived Circulating miR-21 Promotes Differentiation of Monocytes into Osteoclasts</p>

Abstract: Osteoclastogenesis is a key process in osteolytic bone metastasis (BM). Previous studies indicated that some miRNAs could regulate cancers progression and osteoclastogenesis. Our purpose was to investigate the roles of lung cancer cells-derived circulating miR-21 on osteoclastogenesis and its clinical significance in BM patients. Materials and Methods: The difference of miRNA expression in two lung cancer cell lines SBC-5 (with characteristic BM ability) and SBC-3 (without BM ability) were analyzed by microarr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 55 publications
1
11
0
Order By: Relevance
“…miR-21, a highly conserved oncomicroRNA, is expressed in serum of many types of cancer patients, including hepatocellular carcinoma, lung cancer, and breast cancer, which is significantly higher than that in healthy controls 29 - 31 . Several studies demonstrate that miR-21 involves in tumor progression and osteoclasts differentiation 32 , 33 . For example, miR-21 promotes NFATc1 up-regulation during osteoclast differentiation by directly binding programmed cell death 4 (PDCD4), which has a suppressive function on c-Fos transactivation 34 .…”
Section: Introductionmentioning
confidence: 99%
“…miR-21, a highly conserved oncomicroRNA, is expressed in serum of many types of cancer patients, including hepatocellular carcinoma, lung cancer, and breast cancer, which is significantly higher than that in healthy controls 29 - 31 . Several studies demonstrate that miR-21 involves in tumor progression and osteoclasts differentiation 32 , 33 . For example, miR-21 promotes NFATc1 up-regulation during osteoclast differentiation by directly binding programmed cell death 4 (PDCD4), which has a suppressive function on c-Fos transactivation 34 .…”
Section: Introductionmentioning
confidence: 99%
“…The pro-osteoclastic function of miR-21 is further demonstrated in vivo using miR-21 knockout mice, in which miR-21 deficiency inhibits bone resorption and osteoclastogenesis via targeting PDCD4 (Hu et al, 2017). miR-21 is found to be downregulated by bisphosphonate in lung cancer patients with osteolytic bone metastasis (Zhao et al, 2020). Another study revealed that estrogen suppresses miR-21 biogenesis, leading to upregulation of Fas Ligand (FasL), which is a target of miR-21 in osteoclasts and induces osteoclast cell death in an autocrine manner (Sugatani and Hruska, 2013).…”
Section: Mirnas That Positively Regulate Osteoclastogenesis Mir-21mentioning
confidence: 95%
“…In accordance with this, Dong and colleagues indicated that PTEN, a pro-apoptotic factor, is down-regulated when the miR-21 expression is enhanced in TNBC cell line. Additionally, miR-21 has shown to be associated with tumorigenesis and differentiation of osteoclast [179,180]. The miR-21 exhibit its negative effects by targeting programmed cell death 4 protein (PDCD4).…”
Section: Exosome and Tnbc Metastasismentioning
confidence: 99%